2018
DOI: 10.1007/s00213-018-4912-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of somatostatin receptor 2 in the context of antidepressant treatment response in chronic mild stress in rat

Abstract: RationaleThe role of somatostatin and its receptors for the stress-related neuropsychiatric disorders has been widely raised. Recently, we have also demonstrated the involvement of somatostatin receptor type 2-sst2R and dopamine receptor type 2-D2R in stress.ObjectiveIn this context, we decided to find if these receptors are involved in response to antidepressant treatment in animal model of depression—chronic mild stress (CMS).MethodsHere, we report data obtained following 7-week CMS procedure. The specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Drugs that act as selective SST2 receptor agonists, such as L-779,976, have never been tested in clinical trials. Thus, given that SST levels were reported to be lower in the brain of MDD patients and stressed rodents ( Frye et al, 2003 ; Tripp et al, 2011 ), which can be normalized by monoaminergic drugs ( Faron-Gorecka et al, 2016 , 2018 ), and preclinical evidence that SST induces antidepressant-like effects, clinical studies testing the antidepressant potential of selective SST2 receptor analogs with longer half-life merit additional attention.…”
Section: The Gabaergic System As a Therapeutic Target For The Treatmementioning
confidence: 99%
“…Drugs that act as selective SST2 receptor agonists, such as L-779,976, have never been tested in clinical trials. Thus, given that SST levels were reported to be lower in the brain of MDD patients and stressed rodents ( Frye et al, 2003 ; Tripp et al, 2011 ), which can be normalized by monoaminergic drugs ( Faron-Gorecka et al, 2016 , 2018 ), and preclinical evidence that SST induces antidepressant-like effects, clinical studies testing the antidepressant potential of selective SST2 receptor analogs with longer half-life merit additional attention.…”
Section: The Gabaergic System As a Therapeutic Target For The Treatmementioning
confidence: 99%
“…In this study, treatment with somatostatin analogue, i.e., octreotide, led to significant improvement in neuropathic pain manifestations. There have been studies showing that apart from endocrinological effects, octreotide produces a number of beneficial effects in different disease states, including ischemia-reperfusion injury 27 , depression 28 , dementia 29 . Administration of octreotide in the ventrolateral orbital cortex has been shown to produce antinociceptive effects in formalin-induced nociceptive behavior in rats 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the role of SOM receptors in the hippocampus of mice revealed that SSTR2 agonists selectively produced anxiolytic-like behaviors, whereas both SSTR2 and SSTR4 agonists had antidepressant-like effects. Moreover, SSTR2 receptors were sensitive to antidepressant treatment—their changed activity was observed during imipramine administration in the chronic mild stress model of depression [ 117 ]. In SST2KO mice, high corticosterone levels and anxiety were found and depressive-like behaviors were observed in both SST2KO and SST4KO strains [ 116 ].…”
Section: Somatostatin and Som-ins In Neuropathologymentioning
confidence: 99%